Maḥmud yunus wa manhajihi fii ta’liifi al qamuus “‘Arabiy - induunisiy - Yusnani, Yusnani (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2024)
The “Arabic-Indonesian” dictionary by Mahmoud Yunus is one of the most famous and widely used dictionaries in Indonesia. It is also suitable for Arabic language learners, especially for beginners. This research aims to find out the Arabic-Indonesian dictionary by Mahmoud Yunus, the methodology of its composition, and the advantages and disadvantages. The results of this research: the writing of an Arabic-Indonesian dictionary by Mahmoud Yunus in June 1972 to renew the Al-Zahbi dictionary. The methodology of its composition uses the radical alphabet according to the pioneers. The advantages of this dictionary are the ease of searching for words, because the dictionary takes the simplest dictionary system, which is the regular alphabet system, and includes rare or colloquial words that cannot be known using morphological rules. This dictionary includes meanings from the infinitive, plural, feminine, masculine, and others. This dictionary contains illustrated vocabulary by presenting a group of words. It is easy to use and handle because the size of the dictionary is moderate and light. To complete this dictionary, in the last unit you write the method for using it, the brief word table, and the list of references. The disadvantages of this dictionary are that in searching for the word, some words had to be abstracted to the root of the word, but some of them were without abstraction and there is no renewal from the author, so there is no modern modern vocabulary in this dictionary, such as vocabulary about science and technology, and there is no correction on it. Errors in this dictionary are either misidentifications or typographical errors.